Oral ulcerations due to drug medications - Yoshinori Jinbu; Toshio Demitsu (Elsevier, 2014)
Ulcers are common symptoms observed in the oral cavity and some ulcerations are induced by drug medications. When ulcers show typical clinical findings differential diagnosis may be easy, but the exact diagnosis is often difficult. We reviewed differential diagnosis of oral ulcerative diseases, clinical characteristics of drug-induced oral ulcerations and drugs inducing oral ulcerations. Many kinds of drugs have been reported to cause oral ulcerations. Among them, non-steroidal anti-inflammatory drugs are popular and well-known. However, several recent reports have described oral ulceration associated with relatively new drugs for the treatment of chronic disorders such as, diabetes, angina pectoris, rheumatoid arthritis, and osteoporosis. We reviewed these new drugs and also reported typical cases of drug-induced oral ulcerations.